Returning incidental findings from genetic research to children: views of parents of children affected by rare diseases. Issue 10 (19th December 2013) - Kleiderman, Erika; Knoppers, Bartha Maria; Fernandez, Conrad V; Boycott, Kym M; Ouellette, Gail; Wong-Rieger, Durhane; Adam, Shelin; Richer, Julie; Avard, Denise
Abstract : Purpose: To explore parental perceptions and experiences regarding the return of genomic incidental research findings in children with rare diseases. Methods: Parents of children affected by various rare diseases were invited to participate in focus groups or individual telephone interviews in Montreal and Ottawa. Fifteen participants were interviewed and transcriptions were analysed using thematic analysis. Results: Four emergent themes underscored parental enthusiasm for receiving incidental findings concerning their child's health: (1) right to information; (2) perceived benefits and risks; (3) communication practicalities: who, when, and how; and (4) service needs to promote the communication of incidental findings. Parents believed they should be made aware of all results pertaining to their child's health status, and that they are responsible for transmitting this information to their child, irrespective of disease severity. Despite potential negative consequences, respondents generally perceived a favourable risk-benefit ratio in receiving all incidental findings. Conclusions: Understanding how parents assess the risks and benefits of returning incidental findings is essential to genomic research applications in paediatric medicine. The authors believe the study findings will contribute to establishing future best practices, although further research is needed to evaluate the impact of parental decisions on themselves and their child.